2002
DOI: 10.2337/diacare.25.11.2032
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Events in 735 Type 2 Diabetic Patients Who Underwent Screening for Unknown Asymptomatic Coronary Heart Disease

Abstract: OBJECTIVE -To report the cardiac events in type 2 diabetic outpatients screened for unknown asymptomatic coronary heart disease (CHD) and followed for 5 years.RESEARCH DESIGN AND METHODS -During 1993, 925 subjects aged 40 -65 years underwent an exercise treadmill test (ETT). If it was abnormal, the subjects then underwent an exercise scintigraphy. Of the 925 subjects, 735 were followed for 5 years and cardiac events were recorded.RESULTS -At the entry of the study, 638 of the 735 followed subjects had normal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 20 publications
10
64
1
3
Order By: Relevance
“…Studies have shown that diabetic individuals with retinopathy are more likely to have myocardial perfusion defects (11,31,32), poorer coronary flow reserve (33), and lower coronary collateral score (34) than those without retinopathy. Moreover, diabetic retinopathy has also been associated with higher degrees of coronary calcification (35) and more diffuse and severe coronary artery stenosis on angiograms (36).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diabetic individuals with retinopathy are more likely to have myocardial perfusion defects (11,31,32), poorer coronary flow reserve (33), and lower coronary collateral score (34) than those without retinopathy. Moreover, diabetic retinopathy has also been associated with higher degrees of coronary calcification (35) and more diffuse and severe coronary artery stenosis on angiograms (36).…”
Section: Discussionmentioning
confidence: 99%
“…Silent ischemia was significantly related to future coronary events in asymptomatic diabetic patients after 2, 8 years (risk ratio: 21) (Rutter et al, 1999). Similarly, 5-year follow-up of the MISAD (Milan Study on Atherosclerosis and Diabetes) cohort showed that abnormal baseline scintigraphy was associated with fivefold increase in fatal and nonfatal cardiac events (risk ratio: 5,47) (Faglia et al, 2002). Diabetic patients with inducible ischemia on stress myocardial perfusion imaging using single-photon emission computed tomography (SPECT) have a significantly higher annual cardiac death or myocardial infarction rate than nondiabetic patients with ischemia (10% vs. 8%) (Shaw & Iskandrian, 2004).…”
Section: Silent Ischemia -Prevalence and Prognosis In Diabetic Patientsmentioning
confidence: 97%
“…Accordingly comparisons between myocardial perfusion imaging and stress echocardiography have shown a higher sensitivity for myocardial perfusion imaging for the detection of multivessel and single-vessel coronary artery disease (Schinkel et al, 2003). In asymptomatic diabetic patients the rate of silent myocardial ischemia diagnosed by stress myocardial perfusion imaging ranges from 6 to 59% (Zellweger et al, 2004;Faglia et al, 2002;, De Lorenzo et al, 2002;Wackers et al, 2004;Rajagapolan et al, 2005;Vanzetto et al, 1999;Cosson et al, 2004). This wide range in the prevalence of silent ischemia is related to differences in patient selection, stress methodology and imaging techniques.…”
Section: Nuclear Single Photon Emission Computed Tomography (Spect) Mmentioning
confidence: 99%
See 2 more Smart Citations